Apigenin Alleviates Pyroptosis in Lung Adenocarcinoma Cells by Modulating TNF ‐α/ NF ‐ κB Signaling and AIM2 Inflammasome Activation - Kairui Zhu; Yulong Mu; Zhenguo Su; Zhen Yue; Dongyang Wu; Guiwu Qu; Chenyang Jiang; Qing Li; Youjie Li; Ning Xie (Thoracic Cancer, 2026)
ABSTRACT Background Pyroptosis‐related signaling contributes to lung adenocarcinoma (LUAD) progression and prognosis. Apigenin (AP) has anti‐inflammatory and cytoprotective properties, but its effects on pyroptosis‐associated signaling in injured LUAD cells remain unclear. Methods A549 cells were treated with carbonyl cyanide m ‐chlorophenyl hydrazone (CCCP) and ferrous sulfate (FeSO 4 ) to establish a cellular injury model. Cell morphology, Cell Counting Kit‐8 signals, and pyroptosis‐associated proteins were assessed after AP treatment. Network pharmacology, molecular docking, molecular dynamics simulations, and analyses of The Cancer Genome Atlas and Gene Expression Omnibus datasets were used to prioritize candidate targets, characterize pyroptosis‐related genes, and develop a prognostic signature. Results CCCP/FeSO 4 reduced CCK‐8 signals and induced morphological injury, whereas AP partially reversed these changes. AP also reduced alterations in GSDMD‐N, caspase‐1, IL‐1β, TNF‐α/NF‐κB pathway proteins, AIM2, and ASC. TNF was prioritized as a candidate target, and computational analyses predicted a potentially stable AP–TNF interaction without demonstrating direct binding. Bioinformatic analyses identified distinct pyroptosis‐related LUAD subgroups and generated a prognostic signature that stratified survival in training and external validation cohorts. AIM2 was additionally prioritized as a LUAD‐ and stress‐associated candidate. Conclusion AP attenuated CCCP/FeSO 4 ‐induced injury and pyroptosis‐associated molecular changes in A549 cells, potentially through TNF‐α/NF‐κB and AIM2‐related signaling. Further mechanistic validation is required.